Evaluasi Program Pendataan Nasional Menuju Indonesia Digital 2045 - Ichtiar, Akbar; Marefanda, Nodi (Sanger Journal: Social, Administration and Government Review, 2025)
This research aims to evaluate the policy implementation of the One Data Marine and Fisheries Program “(Satu Data-KP)” and its relevance to the efforts towards realizing Digital Indonesia 2045. This study employs a qualitative method with a descriptive approach and was conducted in Aceh Province. Data collection utilized observation, interviews, documentation, and audiovisual records. The collected data were subsequently analyzed using methods of data reduction, data presentation, and conclusion drawing. The research critically assesses the program's level of Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Appropriateness. The findings indicate that, in terms of data collection, the program has had a positive impact on decision-making and enhanced service efficiency. However, the program still presents fundamental shortcomings, such as the limited scope of digital transformation being undertaken and the minimal effort to enhance community readiness toward an inclusive, empowering, and sustainable Digital Indonesia.